Dopuszczalność przesłuchania w charakterze świadka radcy prawnego pełniącego funkcję rzecznika dyscyplinarnego w kontekście konstytucyjnego prawa do sądu - Gębusia, Iwona (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
Artykuł dotyczy dopuszczalności przesłuchania w charakterze świadka radcy prawnego pełniącego funkcję rzecznika dyscyplinarnego w kontekście konstytucyjnego prawa do sądu. Prawo do sądu jest zakorzenione w prawie publicznym. Z uwagi na walor konstytucyjny prawa do sądu wyjątki (np. zakaz przesłuchiwania w charakterze świadka radcy prawnego) muszą być interpretowane w sposób ścisły i dodatkowo wynikać z ustawy. Tego typu ograniczenia nie mogą być wykładane rozszerzająco na podstawie tylko postanowień dokumentów prywatnych przyjmowanych przez organy samorządu zawodowego. Dodatkowo wspomniane restrykcje powinny być uzasadnione interesem publicznym (przede wszystkim interesem klienta, a nie np. interesem partykularnym samorządu zawodowego).

The article pertains to the admissibility of hearing as a witness attorney at law acting as a disciplinary ombudsman in the context of the constitutional right to a fair trial. The right to a fair trial is rooted in public law. Due to the constitutional value of the right to a court, exceptions (e.g., the prohibition of questioning as a witness an attorney at law) must be interpreted strictly and additionally result from statutory law. Such restrictions cannot be interpreted extensively on the basis of only the provisions of private documents adopted by the bodies of professional self-government. Additionally, the aforementioned restrictions should be justified by the public interest (first of all, the interest of the client, and not, for example, the particular interest of the professional self-government).
Admissibility of hearing as a witness attorney at law as a disciplinary ombudsman in the context of the constitutional right to a fair trial
Keywords: radca prawny; świadek; prawo do sądu; samorząd radców prawnych; odpowiedzialność dyscyplinarna; attorney at law; witness; the right to a fair trial; professional self-government of attorneys at law; disciplinary liability